2018
DOI: 10.5603/kp.a2018.0054
|View full text |Cite
|
Sign up to set email alerts
|

Clinical usefulness of epicardial adipose tissue in patients with high-intermediate pre-test probability for coronary artery disease

Abstract: In patients with high-intermediate PTP, EAT is a useful measurement that may assist in risk stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
(26 reference statements)
0
6
0
1
Order By: Relevance
“…On the other hand, epicardial adipose tissue quality and quantity (thickness) is related with CAD and may help in risk stratification. [7] We found no differences in the expressions of the following genes between both fat depots: Angiotensinogen, Glucagon-Like-Peptide Receptors type 1 and 2, Phospholipid Transfer Protein, Adiponectin and Uncoupling Protein-1. Given the patients characteristics, we found that diabetes was associated with increased UCP-1 and AGT in PVAT-IMA.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…On the other hand, epicardial adipose tissue quality and quantity (thickness) is related with CAD and may help in risk stratification. [7] We found no differences in the expressions of the following genes between both fat depots: Angiotensinogen, Glucagon-Like-Peptide Receptors type 1 and 2, Phospholipid Transfer Protein, Adiponectin and Uncoupling Protein-1. Given the patients characteristics, we found that diabetes was associated with increased UCP-1 and AGT in PVAT-IMA.…”
Section: Discussionmentioning
confidence: 53%
“…[3] However, the perivascular adipose tissue (PVAT) releases adipokines and other relaxing genes. [4,5] Visceral and epicardial adiposity revealed closer association with cardiovascular (CV) risk compared to subcutaneous fat accumulation, [6,7] possibly due to the stronger immune cell infiltration and higher expression of proinflammatory cytokines in this adipose tissue depot. [8] Although recent papers suggested an important role of (PVAT) in arterial atherosclerosis, the internal mammary artery (IMA) is the exception and shows nearly no atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…Thirty-one studies were excluded for various reasons after reviewing the original text. In 13 studies, the EFT had been measured using a tool other than echocardiography, or CAD had been detected by a non-angiographic method ( 14 26 ). In 8 studies, the parameters required to enter meta-analysis were not reported ( 27 34 ).…”
Section: Resultsmentioning
confidence: 99%
“…4 What is more, growth factors released from inflammatory cells (eg, monocytes) that attack the ischemic region in angiogenesis and arteriogenesis are also involved in this process. 1,3,13,14 Some cytokines initiate an inflammatory response by activating transcription factors. This stimulates the endothelium, resulting in a prompt release of presynthesized and stored molecules such as von Willebrand factor, P -selectin, CD63, interleukin 8, endothelin-1, tissue plasminogen activator, and Ang-2.…”
Section: Methods Study Design and Populationmentioning
confidence: 99%
“…2,3 Arteriogenesis INTRODUCTION Coronary artery disease (CAD) is the leading cause of mortality and morbidity worldwide. 1 In the clinical prognosis of CAD, the complexity and severity of atherosclerosis is as important as the resistance of the heart to ischemia. The myocardial tissue with a sufficiently rich collateral network is more resistant to ischemia.…”
mentioning
confidence: 99%